The mediation of news framing between public trust and nuclear risk reactions in post-Fukushima China: A case study. Issue 2 (1st February 2021) - Qiu, Hongfeng; Weng, Suwei; Wu, Michael Shengtao
Abstract: Although China has become the world's most ambitious country in adopting nuclear energy, few studies have investigated the role of communication behind public acceptance of nuclear risk in this country. This study explored the association of Chinese newspapers' framing of nuclear power with public trust in government and their reactions to nuclear risk. The results revealed that the more the respondents identified with the news framing, the more trust they placed in the government regarding nuclear risk control (NRC). Public identification with news framing also mediated the effect of trust in government on risk perceptions and acceptance. Because online news distribution in China is primarily limited to official news organizations, official discourses about nuclear risk have yet to be substantially challenged in cyberspace. These findings suggest that the enduring, positive news framing, which is guaranteed by China's ubiquitous information control, has greatly contributed to the country's nuclear energy blueprint. However, a trust-based model of risk communication that is facilitated by propaganda and information control may stem 'healthy scepticism' about the large-scale deployment of nuclear energy facilities. This study thus reminds policymakers to review the performance of their risk communication policies and to consider the necessity and proper methods of public risk engagement.